Iron deposition in the precuneus is correlated with mild cognitive impairment in patients with cerebral microbleeds: A quantitative susceptibility mapping study - Tu, Jing; Yan, Jin; Liu, Juan; Liu, Dandan; Wang, Xiaomeng; Gao, Fei (Frontiers in Neuroscience, 2022)
Purpose The purpose of this study was to define whether mild cognitive impairment (MCI) is associated with iron deposition in rich-club nodes distant from cerebral microbleeds (CMBs) in patients with cerebral small vessel disease (CSVD). Methods A total of 64 participants underwent magnetic resonance imaging (MRI) scanning and were separated into three groups, namely, CMB(+), CMB(–), and healthy controls (HCs). We compared their characteristics and susceptibility values of rich-club nodes [e.g., superior frontal gyrus (SFG), precuneus, superior occipital gyrus (SOG), thalamus, and putamen]. We then divided the CMB(+) and CMB(–) groups into subgroups of patients with or without MCI. Then, we analyzed the relationship between iron deposition and MCI by comparing the susceptibility values of rich-club nodes. We assessed cognitive functions using the Montreal Cognitive Assessment (MoCA) and quantified iron content using quantitative susceptibility mapping (QSM). Results In the putamen, the CMB(+) and CMB(–) groups had significantly different susceptibility values. Compared with the HCs, the CMB(+) and CMB(–) groups had significantly different susceptibility values for the SFG and SOG. In addition, we found significant differences in the putamen susceptibility values of the CMB(+)MCI(+) group and the two CMB(–) groups. The CMB(+)MCI(+) and CMB(+)MCI(–) groups had significantly different precuneus susceptibility values. The binary logistic regression analysis revealed that only higher susceptibility values of precuneus were associated with a cognitive decline in patients with CMBs, and it indicated statistical significance. Conclusion Iron deposition in the precuneus is an independent risk factor for MCI in patients with CMBs. CMBs might influence iron content in remote rich-club nodes and be relevant to MCI.